2022
DOI: 10.1038/s41467-022-31751-0
|View full text |Cite
|
Sign up to set email alerts
|

Ciliary transition zone proteins coordinate ciliary protein composition and ectosome shedding

Abstract: The transition zone (TZ) of the cilium/flagellum serves as a diffusion barrier that controls the entry/exit of ciliary proteins. Mutations of the TZ proteins disrupt barrier function and lead to multiple human diseases. However, the systematic regulation of ciliary composition and signaling-related processes by different TZ proteins is not completely understood. Here, we reveal that loss of TCTN1 in Chlamydomonas reinhardtii disrupts the assembly of wedge-shaped structures in the TZ. Proteomic analysis of cili… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 65 publications
1
12
0
Order By: Relevance
“…We also checked a transition zone protein, NPHP4, in BCI-treated cells. Previous studies have found that altered NPHP4 expression decreases IFT velocity, changes protein composition in the cilium, and disrupts ciliary protein entry (Awata et al, 2014;Wang et al, 2022). In both steady-state and regenerating cells with BCI, NPHP4 still localized as two puncta at the transition zone, which supports the unaltered structure visualized with EM, though NPHP4 immunofluorescence was decreased (Fig 4B and C).…”
Section: Bci Inhibits Kap-gfp Protein Synthesissupporting
confidence: 78%
“…We also checked a transition zone protein, NPHP4, in BCI-treated cells. Previous studies have found that altered NPHP4 expression decreases IFT velocity, changes protein composition in the cilium, and disrupts ciliary protein entry (Awata et al, 2014;Wang et al, 2022). In both steady-state and regenerating cells with BCI, NPHP4 still localized as two puncta at the transition zone, which supports the unaltered structure visualized with EM, though NPHP4 immunofluorescence was decreased (Fig 4B and C).…”
Section: Bci Inhibits Kap-gfp Protein Synthesissupporting
confidence: 78%
“…Furthermore, since KIF13B was shown to regulate ciliary localization of CAV1 and interacted with NPHP4 at the ciliary transition zone (Schou et al, 2017), a more direct role for KIF13B-CAV1-NPHP4 interactions in promoting ciliary membrane homeostasis and EV release can be envisioned. In this context we note that mutations in NPHP4 were shown to affect ciliary EV release in C. reinhardtii (Wang et al, 2022) and C. elegans (Wang et al, 2023a), and CAV1 was implicated in ciliary PC2 homeostasis in C. elegans (Scheidel et al, 2018) and in EV biogenesis in other contexts (Ariotti et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Images of cells were captured using an FV3000 confocal microscope (Olympus) with a 40×/NA1.4 oil objective lens (Olympus). The fluorescence intensity was calculated by multiplying the fluorescence intensity by the region of interest (ROI) and corrected for local background intensity with Fiji software (NIH) (Wang et al, 2022). At least three independent experiments were carried out for quantitation or statistical analyses.…”
Section: Methodsmentioning
confidence: 99%